Discursos mediáticos sobre la diferencia en América Latina y el Caribe - Hoff, Tânia (Atlántica de comunicación, 2017)
Divided into three sections, this book explores the discourses on the creation of difference between Latin American and the Caribbean, what actors participate, and what are related social practices. Media discourses on poverty and racism are addressed as well as ways in which certain discourse criminalizes marginalized and socially vulnerable groups.